2015
DOI: 10.7314/apjcp.2015.16.4.1361
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers for Diagnosis of Gastric Cancer by Bioinformatics

Abstract: Background: We aimed to discover potential gene biomarkers for gastric cancer (GC) diagnosis. Materials and Methods: Genechips of 10 GC tissues and 10 gastric mucosa (GM, para-carcinoma tissue, normal control) tissues were generated using an exon array of Affymetrix containing 30,000 genes. The differentially expressed genes (DEGs) between GC tissues and normal control were identified by the Limma package and analyzed by hierarchical clustering analysis. Gene ontology (GO) and pathway enrichment analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…NCAPG has been reported to be a mitotic gene, and its overexpression is responsible for the cell proliferation and migration in hepatocellular carcinoma [ 36 ]. Consistent with our study, NCAPG is differentially expressed in GC tissues compared to normal control tissues, and is enriched in the cell cycle term [ 37 ]. Therefore, we speculated that the downregulation of miR-193b-3p might contribute to GC cell proliferation by mediating the upregulation of NCAPG .…”
Section: Discussionsupporting
confidence: 91%
“…NCAPG has been reported to be a mitotic gene, and its overexpression is responsible for the cell proliferation and migration in hepatocellular carcinoma [ 36 ]. Consistent with our study, NCAPG is differentially expressed in GC tissues compared to normal control tissues, and is enriched in the cell cycle term [ 37 ]. Therefore, we speculated that the downregulation of miR-193b-3p might contribute to GC cell proliferation by mediating the upregulation of NCAPG .…”
Section: Discussionsupporting
confidence: 91%
“… 13 15 , 19 24 , 35 In this report, CCNB1 and CCNB2 were upregulated in GC, which was consistent with previous studies. 35 , 52 54 The CCNB1 mRNA overexpression was also confirmed in different GC Lauren subtypes, which indicated that CCNB1 might be helpful to guide GC classification. Relevant research showed that overexpression of CCNB1 was associated with clinical stage, 54 lymph lode metastasis, 35 , 53 , 54 and poor survival in GC patients.…”
Section: Discussionmentioning
confidence: 83%
“…High level of CCNB1 expression has been detected in a variety of cancers [2226], including GC [27], resulting in uncontrolled cell growth. A recent study reported that cyclin B1 and cyclin B2 were the most significant candidate biomarkers in GC [28]. …”
Section: Discussionmentioning
confidence: 99%